Wage Effects of Educational Mismatch According to Workers' Origin: The Role of Demographics and Firm Characteristics - Valentine Jacobs; François Rycx; Mélanie Volral (Global Labor Organization (GLO), 2021)
This paper analyses the wage effects of educational mismatch by workers' origin using a sizeable, detailed matched employer-employee dataset for Belgium. Relying on a fine-grained approach to measuring educational mismatch, the results show that over-educated workers, regardless of their origin, suffer a wage penalty compared to their well-matched former classmates. However, the magnitude of this wage penalty is found to vary considerably depending on workers' origin. In addition, the estimates show that origin-based differences in over-education wage penalties significantly depend on both demographics (workers' region of birth, education, and gender) and employer characteristics (firm size and collective bargaining).
Keywords: I24; I26; J15; J24; J31; 330; Immigrants; educational mismatch; wage gap; linked employer-employee data